Skin innervation: review - Ständer, Sonja; Schmelz, Martin (The journal of investigative dermatology, 2024)
All layers and appendages of the skin are densely innervated by afferent and efferent neurons providing sensory information and controlling skin perfusion and sweating. In mice, neuronal functions have been comprehensively linked to unique single-cell expression patterns and to characteristic arborization of nerve endings in skin and dorsal horn, whereas for humans, specific molecular markers for functional classes of afferent neurons are still lacking. Moreover, bidirectional communication between sensory neurons and local skin cells has become of particular interest, resulting in a broader physiological understanding of sensory function but also of trophic functions and immunomodulation in disease states.